What is the impact of an exogenous shock to the wage share? VAR results for the US economy, 1973-2018 - Deepankar Basu; Leila Gautham (University of Massachusetts, Department of Economics, 2019)
This paper uses a novel empirical strategy to present empirical estimates of the effect of an exogenous shock to distribution on demand and accumulation for the US economy from 1973 to 2018. We use recursive vector autoregressions to identify the impact of shocks to the wage share. We impose restrictions motivated by a simple neo-Kaleckian openeconomy model, and build on the recursive identification scheme in Christiano, Eichenbaum and Evans (1999) to show that this small set of plausible and transparent assumptions are sufficient to identify the impact of shocks to distribution. We find that positive shocks to the wage share have long-lasting negative impacts on demand and growth. Our results are robust to the inclusion of additional variables and to differences in specification.
Keywords: D3; C32; E25; 330; Demand-distribution dynamics; neo-Kaleckian models; functional income distribution; VAR estimation